2017
DOI: 10.1002/ejhf.798
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure with mid‐range ejection fraction: a distinct clinical entity? Insights from the Trial of Intensified versus standard Medical therapy in Elderly patients with Congestive Heart Failure (TIME‐CHF)

Abstract: Although the 'intermediate' clinical profile of HFmrEF between HFrEF and HFpEF would support the conclusion that HFmrEF is a distinct clinical entity, we hypothesize that HFmrEF has to be categorized as HFrEF because of the high prevalence of coronary artery disease and the similar benefit of NT-proBNP-guided therapy in HFrEF and HFmrEF, in contrast to HFpEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
149
6
15

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(185 citation statements)
references
References 29 publications
15
149
6
15
Order By: Relevance
“…Our findings are in line with those from Lam and Solomon, albeit in a much larger group of patients, suggesting patients with HFmrEF have heavy representation of risk factors for-or established-vascular disease. 17,18 Heart failure with preserved EF may also have unique characteristic physiological responses to exercise as well, and recently, a study by Pugliese and colleagues examined patients with HFrEF, HFmrEF, and HFpEF and demonstrated BMI, body mass index; b.p.m., beats per minute; CABG, coronary artery bypass graft; EF, ejection fraction; HF, heart failure; HFmrEF, heart failure with mid-range ejection fraction; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection fraction; LVEF, left ventricular ejection fraction; PCI, percutaneous intervention; PTCA, percutaneous transluminal coronary angioplasty; SD, standard deviation. In a 2007 analysis of 41 267 registry patients, characteristics of patients with LVEF between 40 and 50% were closer to those of patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with those from Lam and Solomon, albeit in a much larger group of patients, suggesting patients with HFmrEF have heavy representation of risk factors for-or established-vascular disease. 17,18 Heart failure with preserved EF may also have unique characteristic physiological responses to exercise as well, and recently, a study by Pugliese and colleagues examined patients with HFrEF, HFmrEF, and HFpEF and demonstrated BMI, body mass index; b.p.m., beats per minute; CABG, coronary artery bypass graft; EF, ejection fraction; HF, heart failure; HFmrEF, heart failure with mid-range ejection fraction; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection fraction; LVEF, left ventricular ejection fraction; PCI, percutaneous intervention; PTCA, percutaneous transluminal coronary angioplasty; SD, standard deviation. In a 2007 analysis of 41 267 registry patients, characteristics of patients with LVEF between 40 and 50% were closer to those of patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…[170][171][172][173][174][175][176] With Highlights in heart failure respect of outcomes, prognosis of the patients with HFmrEF is slightly better than that of the patients with HFrEF in most, but not all, 177 of the studies. a LVEF between 40% and 49% (HFmrEF).…”
Section: Heart Failure With Mid-range Ejection Fractionmentioning
confidence: 99%
“…Although clinical entity of chronic HF with reduced LV ejection fraction (EF) < 40% (HFrEF) and preserved LVEF = 50-59% (HFpEF) respectively has defined, there is not completely clear whether HF (HFmrEF) related to mid-range LVEF=40-49% could associate with clinical outcomes and prognosis similar other phenotypes of chronic HF [6]. The analysis of the TIME-CHF (Trial of Intensified versus standard Medical therapy in Elderly patients with Congestive Heart Failure) trail yielded that clinical status, profile of comorbidities including CAD and impaired quality of life of individuals with HFmrEF were comparable to patients with HFrEF, but these patients were not similar HFpEF in these fields [7]. In the Swedish Heart Failure Registry a higher adjusted risk of all-cause death and CV death in patients with HFmrEF and HFrEF versus HFpEF was defined [8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is overlapping in clinical and biomarker-based prediction of outcomes in different HF phenotypes [9,10]. Indeed, natriuretic peptides (NPs) and cardiac troponins strongly predicted HFrEF and HFmrEF, but not HFpEF, although galectin-3 and soluble ST2 yielded much accurate predictive values for newly diagnosed HFpEF / HFmrEF and HFrEF-related admission to the hospital [7,9]. Recent clinical trial has shown that biomarker-guided therapy based on serial measure of N-terminal pro-B-type NP (NT-proBNP) in comparison with standard HF therapy resulted in improved survival free of chronic HF admissions in HFrEF and HFmrEF, but not in HFpEF [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation